Building an entrepreneurial ecosystem through Open Innovation fostered by public policies - Juan R. Campos-Blázquez; Sandra Martín-García; Mar Cárdenas-Mu\~noz (Journal of Innovation & Knowledge (JIK), 2024)
Entrepreneurial ecosystems (EEs) are a growing focus for policymakers and academics seeking to foster innovation and economic growth. While existing literature has analysed various aspects of EEs, limited research has examined how public policies can contribute to their development. Through a single-case study, this study addresses this gap by analysing the role of a regional government in overcoming the challenges of building an EE. We explore the creation and development of the Biscay Startup Bay (BSB) EE in Bilbao City (Bizkaia, Basque Country, Spain). We describe the unique framework that they crafted and implemented, highlighting the key attributes that generate value for all stakeholders. This single-case study of the BSB EE in Spain offers valuable insights for policymakers seeking to design and implement successful Open Innovation-driven approaches to creating and developing regional EEs.
Keywords: H20; H27; L26; L38; O36; 650; Entrepreneurial ecosystem; Public policies; Open Innovation; Entrepreneurship; Stakeholders